Is Chronic Sildenafil Therapy Safe and Clinically Beneficial in Patients With Systolic Heart Failure?. Issue 2 (12th December 2012) - Amin, Ahmad; Mahmoudi, Ebrahim; Navid, Hossein; Chitsazan, Mitra
<x xml:space="preserve">Abstract</x> Sildenafil is a selective phosphodiesterase‐5 inhibitor and causes vasodilatation, particularly in pulmonary circulation. Since left heart failure may be associated with pulmonary hypertension "out of proportion to left heart disease, " sildenafil may have beneficial effect in such patients. The present investigation was designed as a 12‐week, single‐center, randomized, double‐blind, placebo‐controlled study evaluating the effects of sildenafil on mean blood pressure (primary endpoint) in patients with left systolic heart failure. Secondary endpoints included exercise capacity assessed by 6‐minute walk test. A total of 106 patients were randomized 1:1 to sildenafil (n=53) or placebo (n=53). Patients received sildenafil 25 mg twice a day or matching placebo for the first 2 weeks and 50 mg 3 times a week for the remainder of the trial. The placebo‐corrected effect on mean blood pressure was 1.16 mm Hg (95% confidence interval, −1.6 to 5.1, P >.05), demonstrating that sildenafil did not decrease mean blood pressure. Compared with placebo, sildenafil increased the 6‐minute walk test by a nonsignificant treatment effect of 14 m (P=.67). Adverse effects occurred in a comparable proportion of patients taking sildenafil and placebo, and none of the patients needed to discontinue therapy. Sildenafil is well tolerated in left heart failure patients and does not decrease blood pressure. It can be safely added to standard heart failure therapy.